Swift declines predicted following mating system changes driven by an introduced predator. Issue 4 (8th April 2019) - Wright, Timothy F.
Abstract: In Focus: Heinsohn, R., Olah, G., Webb, M., Peakall, R., &Stojanovic, D. (2019 ).Sex ratio bias and shared paternity reduce individual fitness and population viability in a critically endangered parrot .Journal of Animal Ecology, 88, 502 –510 . While the effects of variation in the sex ratio of offspring have been thoroughly explored over the last century, the sex ratio of adults has received far less attention. A paper by Heinsohn and colleagues in this issue shows that changes in the adult sex ratio can have striking effects on mating systems, reproductive success and population viability. These impacts are all the more dramatic because they occur in a critically endangered species, the swift parrot, Lathamus discolor, of Tasmania. This species suffers heavy predation from the introduced sugar glider, Petaurus breviceps, which kills nesting females and their clutches, resulting in strongly male‐biased adult sex ratios. The authors combined demographic and genetic data to show that, at sites with heavier predation, the remaining females were more likely to mate with multiple males. This shift in the mating system also led to lower overall nesting success, with fewer chicks fledged per nest at sites with higher levels of mixed paternity. Population viability models based on these data predicted steep population declines, with models using the highest observed rates of mixed paternity showing the sharpest declines. These results demonstrate that changes in the adult sex ratio can have far‐reaching impacts, including on the fitness of populations themselves. Abstract : This In Focus highlights the striking effects of predator‐induced changes in mating system on the population fitness of an endangered parrot described in Heinsohn et al. (2019 ).